English Growth and yield of Brazilian potato cultivars - Lenz, Emerson Andrei; Pereira, Arione da Silva; Reisser Junior, Carlos; Cuadra, Santiago Vianna; Azevedo, Fernanda Quintanilha; Silva, Giovani Olegário da; Cima, Francieli Fátima; Silva, Tuane Araldi da; Wolter, Daiana Döring (Comunicata Scientiae, 2024)
The analysis of plant growth of cultivars is useful for understanding the dynamics of accumulation and partition of photoassimilates during the crop cycle, and this information is important for the crop management of each cultivar. The objective of this study was to evaluate potato cultivars BRS Ana, BRSIPR Bel, BRS Clara, BRS F63 (Camila) and Macaca for growth and yield, under subtropical climatic conditions of Southern Brazil. Plant samples were collected every 20 days, beginning 40 days after planting (DAP), totaling five collections, and physiological growth indexes and the dry mass partitioning to plant organs were estimated. ‘BRSIPR Bel’ showed the fastest development of assimilatory system. ‘BRS Ana’ had the most vigorous plants and the largest leaf area, reaching the leaf area index 4.0 at 70 DAP. ‘BRSIPR Bel’ e ‘BRS Ana’ had the highest dry mass yield, 214 g and 206 g of dry mass plant-1, respectively. ‘BRS F63’ (Camila) and ‘BRSIPR Bel’ presented earlier tuberization and were the most efficient cultivars in the partitioning of dry mass to tubers, with the highest coefficient of dry mass partitioning to tubers estimated between 40 and 64 DAP. These two cultivars also showed the highest yield of marketable tubers.